A four-step plan for curriculum design…. (2nd January 2020) - Bromley, Matt
Abstract : The new Ofsted Education Inspection Framework has thrust the curriculum into the spotlight. The intent, implementation and impact of what we teach are under scrutiny as inspectors look for a broad and balanced curriculum. Matt Bromley offers us a four-step plan for curriculum design and asks some key questions about what we teach…